Efek Pemberian Biskuit Ikan Patin (Pangasius hypophthalmus) Dengan Jenis Tepung Yang Berbeda Terhadap Pertambahan Berat Tubuh Mencit - Firlianty Firlianty (EnviroScienteae, 2020)
The objective of the study was to know the effect of biskuit made of different flour materials mixed with catfish (Pangasius hypophthalmus) on the body weight increment of rat. This study was conducted from January - May 2020 under an experimental method. It used Complete Randomized Design with 4 treatments and 3 replications: catfish biskuit processed with flour (O), tapioca (A), rice flour (B), cornstarch (C). Results showed that the administration of catfish (Pangasius hypophthalmus) biscuit processed with different flour highly significantly influenced the weight increment of the rat.